Pengaruh Kepemimpinan, Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan PT. Prisma Cipta Mandiri Sungai Bungur Estate Kecamatan Kikim Timur Kabupaten Lahat - Lesi Agusria; Zawawi Nasution; Ecy Puspita (P3M STIE Mulia Darma Pratama, 2020)
This research aims to determine the influence of leadership, motivation and work discipline towards employee Kineeja PT. Prisma Cipta Mandiri Sungai chamur Estate in District Kikim Timur Lahat District. This type of research is associative research, using 12 indicators on performance variables. The population in this study is all employees of the land section of PT Prisma Cipta Mandiri Sungai chamur Estate in District Kikim Timur Lahat District. The samples were determined by a sampling cluster method technique, with respondents as much as 84 people. The method of data collection used is a questionnaire technique (poll). The data analysis method used is a method of multiple linear analyses. In the results of research obtained by using SPSS, shows the test results F there is a significant influence of leadership, motivation and work discipline together towards employee performance as well as results t test est (partial) also showed there is a significant influence of leadership, Motivation and Discipline towards employee performance of PT.Prisma Cipta Mandiri Sungai Bungur Estate di Kecamatan Kikim Timur Kabupaten Lahat.